BAHASA DAN KETIMPANGAN GENDER - Jaeni, Muhammad (IAIN Pekalongan, 2009)
Gender inequality not only shows up in the legal, social or purely political, but also gender discrimination in the field of human language which can automatically give birth to living systems which tend to marginalization of women. Gender inequality is in the field of linguistics partly contained in, the assumption of women’s language, mastery of the language gap between men and women, texts and language learning systems, and poor language skills and logic.